Exploring the informal learning of zero waste lifestyle in Malaysia with big data analytics - Nur Suhaila Zulkifli; Latifah Abd Manaf (Cleaner and Responsible Consumption, 2024)
Malaysia's solid waste generation is showing a worrying increasing trend, while public awareness towards achieving zero waste remains low. As a big data resource, social media gives valuable insight into the public's perspective on zero waste and, as such, may be fully utilized as an active informal learning platform to lessen the reliance on formal environmental education. Using big data analytics on Instagram, this study aimed to assess the public knowledge, attitude and practice concerning zero waste lifestyle in Malaysia in order to develop an informal learning strategy on social media. Purposive data sampling was conducted on Phantombuster using zero waste-related Instagram hashtags, which yielded 1723 high engagement posts and 1500 comments from 35 identified hashtags. The recorded posts were analyzed using descriptive statistics and sentiment analysis on Python's TextBlob. A total of 94.3% of posts were published by public and private sector accounts, highlighting their vital role in facilitating active knowledge sharing across the online zero waste communities. The sentiment analysis results indicated 41.3% of comments were fairly positive, while 36.1% were more objective and knowledge oriented, acknowledging the collective individual actions that have initiated influential social change in Malaysia. This study advances the existing literature on zero waste and informal learning by recommending the use of big data analytics on social media in the local context. Only with full commitment from all parties to raising public awareness about waste management will the zero waste nation be realized.